2015
DOI: 10.1007/s00595-015-1125-3
|View full text |Cite
|
Sign up to set email alerts
|

A lower neutrophil to lymphocyte ratio is closely associated with catarrhal appendicitis versus severe appendicitis

Abstract: The preoperative NLR in patients undergoing appendectomy is closely associated with CA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
45
1
8

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 31 publications
4
45
1
8
Order By: Relevance
“…There are very little studies on this subject, yet it is reported that NLR appears to have greater diagnostic accuracy than traditional diagnostic laboratory tests (either white blood cell or C-reactive protein alone). Additionally, it is reported that NLR on admission to the hospital is an independent predictor of positive appendicitis histology (19). Nowadays, some authors report that the NLR is a predictor of inflammation and helpful in the preoperative diagnosis of AA (21,23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are very little studies on this subject, yet it is reported that NLR appears to have greater diagnostic accuracy than traditional diagnostic laboratory tests (either white blood cell or C-reactive protein alone). Additionally, it is reported that NLR on admission to the hospital is an independent predictor of positive appendicitis histology (19). Nowadays, some authors report that the NLR is a predictor of inflammation and helpful in the preoperative diagnosis of AA (21,23).…”
Section: Discussionmentioning
confidence: 99%
“…However, its sensitivity is low so leukocyte count is not diagnostic (17,18). Nowadays, some authors demonstrated that the neutrophil to lymphocyte ratio (NLR) is a predictor of inflammation and helpful in the preoperative diagnosis of AA (19)(20)(21). To the best of our knowledge, MPV levels, RDW, NLR and PLR and in patients with AA have not simultaneouly been reported.…”
mentioning
confidence: 99%
“…[4][5][6][7] Shimizu et al [7] suggest a NLR cut-off value of 5.0 for the diagnosis of acute appendicitis, with 44% sensitivity and 22% specificity. Ishizuka et al [5] determined a cut-off value of 8.0 for NLR to differentiate gangrenous appendicitis from catarrhal appendicitis, with 73% sensitivity and 39% specificity.…”
Section: (E)mentioning
confidence: 99%
“…[1,2] However, because these modalities require special equipment and experienced radiologists, surgeons seek simpler means of definitive diagnosis. In the last decade, simple parameters included in a standard complete blood count and routine preoperative tests, including neutrophil count, neutrophil ratio, [3] neutrophil-to-lymphocyte ratio (NLR), [4][5][6][7] platelet count (PLT), [8,9] mean platelet volume (MPV), [8][9][10][11][12][13] and serum bilirubin level, [14][15][16][17][18][19][20] have been studied for potential value in diagnosis of acute appendicitis…”
mentioning
confidence: 99%
“…However when it compared with non-pregnant patients were more increased. In a study revealed that the neutrophil to lymphocyte ratio > 5), fever < 38°C), white blood cell count (28) < 11.5 × 10 3 /mm 3 and serum level of C-reactive protein (< 110 mg/L) is significantly associated with Catarrhal appendicitis [29]. Urine analysis, temperature and anorexia as do as non-pregnant patients were inconclusive.…”
Section: Discussionmentioning
confidence: 99%